Fundamental parameters for the stiffness and strength control of artificially cemented sand - Nilo Cesar Consoli (2009)
The treatment of soils with cement is an attractive technique when the project requires improvement of the local soil for the construction of subgrades for rail tracks, as a support layer for shallow foundations and to prevent sand liquefaction. As reported by Consoli et al. in 2007, a unique dosage methodology has been established based on rational criteria where the voids/cement ratio plays afundamental role in the assessment of the target unconfined compressive strength. The present study broadened the research carried out by Consoli et al. in 2007 through quantifying quantifies the influence of voids/cement ratio on the initial shear modulus G and Mohr-Coulomb effective strength parameters c ,fi of an artificially cemented sand. A number of unconfined compression and triaxial compression tests with bender elements measurements were carried out. It was shown that the void/cement ratio defined as the ratio between the volume of voids of the compacted mixture and the volume of cement is an appropriate parameter to assess both initial stiffness and effective strength of the sand-cement mixture studied.DOI: 10.1061/(ASCE)GT.1943-5606.0000008